2009
DOI: 10.2215/cjn.02280508
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myeloperoxidase and Oxidative α1-Antitrypsin in Patients on Hemodialysis

Abstract: Background and objectives: The present study assesses the effects of the oxidative stress marker, myeloperoxidase (MPO), and the possible MPO-related oxidative stress marker, oxidative ␣ 1 -antitrypsin (oxAT), on carotid intima-media thickness (CIMT) and protein-energy wasting (PEW) in patients on hemodialysis (HD).Design, setting, participants, & measurements: Blood samples were obtained from 383 patients before HD to measure WBC count, serum albumin, lipids, high-sensitivity C-reactive protein (CRP), ␣ 1 -an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
4
28
3
Order By: Relevance
“…On the other hand, a study confirming the association between nutritional state and oxidative stress demonstrated aggravated oxidative stress in PEW patients with low BMI (21). Moreover, levels of oxidized ␣1-antitrypsin, a potential marker of activated neutrophil-associated oxidation includ- ing MPO-catalyzed hypochlorous acid production, seems to be increased in MHD patients with low BMI levels and associated with decreases in GNRI (22). oxHDL may therefore not always be increased in patients with increased fat mass with concomitant oxidative stress but could appear in MHD patients with low BMI and decreased fat.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, a study confirming the association between nutritional state and oxidative stress demonstrated aggravated oxidative stress in PEW patients with low BMI (21). Moreover, levels of oxidized ␣1-antitrypsin, a potential marker of activated neutrophil-associated oxidation includ- ing MPO-catalyzed hypochlorous acid production, seems to be increased in MHD patients with low BMI levels and associated with decreases in GNRI (22). oxHDL may therefore not always be increased in patients with increased fat mass with concomitant oxidative stress but could appear in MHD patients with low BMI and decreased fat.…”
Section: Discussionmentioning
confidence: 87%
“…Krudeiner and Verspaget (2002) showed that oxidative stress occurs with the abundance of free radicals created by leucocytes in the inflammation of intestines, thereby the damage in the inflammatory region progresses. In our study, the MPO values were determined, which are both a measure of inflammation (Loria et al, 2008) and an indicator of oxidative stress with their prooxidant property (Honda et al, 2009). The increase in MPO values in the aluminum group is indicative of the fact that Al might produce free radicals in the small intestine and, therefore, cause oxidative stress and inflammation in the tissues.…”
Section: Discussionmentioning
confidence: 92%
“…2). Therefore, obviously increased EA levels in these patients might be a risk factor for PEW as a consequence of chronic inflammation and oxidative stress [35,36]. …”
Section: Discussionmentioning
confidence: 99%